2020
DOI: 10.21055/preprints-3111821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aprotinin ‐ a new multi-target drug candidate or "magic shotgun" for the therapy of COVID‐19

Abstract: Aprotinin showed high efficacy and safety in a prospective study of combination therapy for hospitalized patients with moderate to severe COVID-19 pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…APR has an antithrombotic mechanism of action, which, in combination with its multilevel anti-inflammatory activity, makes this drug a valuable assistant in COVID-19 treatment. APR can be used alone for the prevention and treatment of COVID-19 [59,66] or in combination with inhibitors of SARS-CoV-2 replication in the host cells [67,68,303,304].…”
Section: Entry Inhibitors Of Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…APR has an antithrombotic mechanism of action, which, in combination with its multilevel anti-inflammatory activity, makes this drug a valuable assistant in COVID-19 treatment. APR can be used alone for the prevention and treatment of COVID-19 [59,66] or in combination with inhibitors of SARS-CoV-2 replication in the host cells [67,68,303,304].…”
Section: Entry Inhibitors Of Sars-cov-2mentioning
confidence: 99%
“…On the Covid19-preprints.microbe.ru platform, a published unreviewed preprint of a prospective clinical trial of the safety and efficacy of APR in the treatment of hospitalized patients with moderate-to-severe COVID-19 pneumonia has also been published [ 59 ]. This study included 23 patients (14 men and 9 women) with an average age of 60.7 ± 8.3 years.…”
Section: Apr For Covid-19 Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in addition to an anti-inflammatory effect, it is suggested that aprotinin can prevent SARS-CoV-2 penetration into susceptible cells and inhibits its replication. Our preliminary case series demonstrated a good potential of aprotinin for prevention [ 11 ] and as a part of combination therapy for the treatment [ 12 ] of COVID-19.…”
Section: Introductionmentioning
confidence: 99%